Soybean and wheat response to lime in no-till Argentinean mollisols - Barbieri, Pablo Andres (2015)
Crop production in Argentina has significantly increased over the past few years; this increase was consequence of better management practices which included P and N fertilization and, occasionally, S fertilization. Commonly used rates, however, are not sufficient to balance nutrients export in grain crops. This situation is particularly negative for meso-nutrients (Ca+2 and Mg+2) because they are not normally applied by farmers. The objective of this study was to determine the effect of lime over four years period on soybean, one year period on wheat and on a one year double cropped wheat/soybean combination on no-till. The experimental design was a randomized complete blocks design with three replications and two combinations of lime (with and without). Results showed that lime application significantly increased soil pH, exchangeable Ca+2 content, and therefore, base saturation and Ca+2 saturation in cation exchangeable capacity (CEC). As average growing seasons, the relative increments due to lime application were 8, 22, 18, and 20% for pH, soil exchangeable Ca+2 content, base saturation and Ca+2 saturation in CEC, respectively. Results showed that soil bulk density and penetration resistance were not affected by lime application. Soil structure stability was significantly affected by lime application. Wheat grain yield was not affected by lime, but soybean grain yield was significantly increased by lime (7% average across year). Cumulative grain yield was significantly increased by lime application indicating that the benefits of liming were cumulative over time (27,556 vs 28,629 kg ha−1 for lime and no lime, respectively). Increments in relative grain yield were not associated with soil pH in both crops; however, significant relationships were determined between relative soybean grain yield and soil Ca+2 content, base saturation and Ca+2 content in CEC. A soil Ca+2 critical concentration of 12.4 meq 100 g−1 was determined to obtain 95% of relative soybean grain yield. The study concluded that soil Ca+2 content would limit soybean grain yield as a consequence of cation unbalance in intensive agriculture soil.